Formulation and Preliminary Evaluation of Natural Hair Colorant - JOSHI UTTARA; BANDE SWAPNALI; UPADHYE MOHINI (International Journal of Pharma and Bio Sciences, 2010)
Loss of colors in hair is due to various reasons like genetic influence, effect of environmental factors, use of alcoholic preparations etc. Though the permanent synthetic hair dyes are available in different ranges and retain natural luster, they have the chief disadvantage of producing hypersensitive reactions in some individuals. From ancient days, various plant materials like Henna, Indigo, Chamomile, Shoe flower etc are used to dye grey hair to get natural black color. But instead of getting black color shades of red to copper color are obtained. A need was felt to formulate a dye containing only plant products which is safe for use and does not have the problems of staining skin during use and hypersensitive reactions. In the present investigation the formulations are developed using different combinations of Henna and Indigo along with other herbs.